Pathology of the calcified zone of articular cartilage in post-traumatic osteoarthritis in rat knees. - Melissa Schultz; Jeremy Molligan; Lew Schon; Zijun Zhang (PLoS ONE, 2015)
This study aimed to investigate the pathology occurring at the calcified zone of articular cartilage (CZC) in the joints afflicted with post-traumatic osteoarthritis (PTOA).Rats underwent bilateral anterior cruciate ligament (ACL) transection and medial meniscectomy to induce PTOA. Sham surgery was performed on another five rats to serve as controls. The rats were euthanized after four weeks of surgery and tibial plateaus were dissected for histology. The pathology of PTOA, CZC area and the tidemark roughness at six pre-defined locations on the tibial plateaus were quantified by histomorphometry.PTOA developed in the knees, generally more severe at the medial plateau than the lateral plateau, of rats in the experimental group. The CZC area was unchanged in the PTOA joints, but the topographic variations of CZC areas that presented in the control knees were reduced in the PTOA joints. The tidemark roughness decreased in areas of the medial plateau of PTOA joints and that was inversely correlated with the Mankin's score of PTOA pathology.Reduced tidemark roughness and unchanged CZC area differentiate PTOA from primary osteoarthritis, which is generally believed to have the opposite pathology at CZC, and may contribute to the distinct disease progression of the two entities of arthropathy.